AB0487 Neurologic manifestations and their impact on chronic damage in patients with antiphospholipid syndrome: result from a monocentric cohort. (15th June 2017) - Mazilu, D; Potarniche, D; Saulescu, I; Borangiu, A; Groseanu, L; Constantinescu, C; Vlad, V; Berghea, F; Bojinca, V; Opris-Belinski, D; Balanescu, A; Predeteanu, D; et al.
Abstract : Background: Antiphospholipid syndrome (APS) is an autoimmune disease with wide clinical features and cumulative damage. The nervous system involvement is very broad and severe. Objectives: The aim of this study is to analyze the impact of neurologic manifestations on Damage Index in Patients with APS (DIAPS). Methods: All consecutive patients known with APS were included in our monocentric cohort. Data on medical history, clinical manifestations, aPL profile and medication were collected. DIAPS score was used to measure damage in each patient. Results: Seventy six patients with APS were included: 11 patients with primary APS and 65 patients with secondary APS, with mean disease duration of 9.59±7.39years. Overall, 35 patients (46.1%) had neurologic manifestations. Their mean disease duration was 9.2±5.76 years. Seven patients had primary APS and 28 patients had secondary APS. Six patients were on chronic oral anticoagulant therapy and low dose aspirin, 12 patients on oral anticoagulant alone and 15 patients on low dose aspirin. Transient ischemic attack was the first manifestation of APS in 4 patients (11.42%) at mean age of 29.5±10.96 years. Their mean DIAPS value was 7.75±4.19. Ischemic stroke was the first APS manifestation in 12 patients (34.28%) at mean age of 40.08±16.31years, with DIAPS mean value of 7.41±3.67. All of these patients have neurological sequelaes. The DIAPS value was higher in patients with neurologic manifestations (3±2.9 vs 5.71±3.62, p=0.001) and DIAPS value correlated significantly to neurologic manifestations (R=0.416, p<0.000) reflecting it's impact on cumulative damage in APS patients. Conclusions: Neurologic manifestations in APS patients have a great impact on cumulative damage especially in patients presenting with ischemic stroke or transient ischemic attack as the first manifestation of APS. References: M-C Amigo et al. Development and initial validation of a damage index (DIAPS) in patients with thrombotic antiphospholipid syndrome (APS). Lupus (2015) 24, 927–934. L.A. Martinez-Martinez et al. Damage Index in Patients with Thrombotic Antiphospholipid Syndrome: Retrospective Cohort Study. Ann Rheum Dis 2016;75:1065. Disclosure of Interest: None declared